PERBANDINGAN UJI KUAT TEKAN BETON MENGGUNAKAN SIRTU DAN BATU SUNGAI KAPUAS HULU DENGAN SIRTU DAN BATU SUNGAI DIPECAH - Fiandi, Fiandi; Nizar, Nizar; wandi, wandi (Jurusan Teknik Sipil Polnep, 2023)
Concrete is a composite material (mixture) of several materials whose basic binder consists of a combinationof fine aggregate, coarse aggregate, water and different additives in a particular mixture. Sand and gravelare fillers that are used together with a binder and water to form a dense, hard mixture. Sand and gravel inthe Mentebah area, Kapuas Regency has the potential because they are easy to obtain.This study aims to compare and determine the value of the compressive strength of concrete produced fromconcrete using gravel and river stone as a substitute for fine aggregate and coarse aggregate from mentebah.The research was conducted on cylindrical specimens measuring 30 cm high and 15 cm in diameter. The testscarried out were testing the compressive strength of concrete at the age of 7 days and 14 days. The test resultsat the age of 7 days for gravel and river stones cannot be used because they do not meet the procedures. Whilethe test results at the age of 14 days for gravel and river stones with sand and river stones broken have anaverage compressive strength of 16 MPa and 21.75 MPa.Keywords: Fine Aggregate (Sirtu), Coarse Aggregate (River Rock), Compressive Strength, Mentebah District